A Case of Hip Chondrosarcoma Metastasis to the Right Ventricle - Cherukumudi, Amulya; Bhagyashree, R.; Hebbale, Ramesh C.; Varadaraju, R. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Background. While primary cardiac tumors occur rarely, it is observed that cardiac metastases are almost 20 times more common. These are, however, observed during autopsy and seldom missed in living patients. Patients with cardiac metastases present commonly with dyspnea on exertion or pleuritic chest pain. Most common site of intracardiac metastases is right atrium. Case presentation. Here we present a case of a 21-year-old male who presented for a routine check-up to the cardiac outpatient department for assessment of fitness for chemotherapy. He was a known case of right hip chondrosarcoma for 2 years, being treated with Ayurvedic medications. He had no symptoms related to the respiratory or cardiac system. He was afebrile during the examination, however, was restricted to a bed due to the pain in his right hip. On evaluation, the patient was diagnosed with a right ventricular thrombus extending to the pulmonary artery (PA) causing an impending pulmonary embolism. On opening the right atrium and PA, we found a loose, whitish-grey mass, adherent to the right ventricular papillary muscle, entangling the chordae. The tricuspid valve leaflets were also found to be tethered to this mass. The mass was found to extend to the PA beyond the leaflets, however, the leaflets were free of the tissue. The mass was extracted piece-meal through right atrium and PA approach. Histopathology revealed metastatic chondrosarcoma tissue. Conclusion. Cardiac metastases of chondrosarcoma are a rare condition, and can be often asymptomatic. Such patients often present with dyspnea, and imaging may not be able to rightly identify the cause. A high index of suspicion is necessary in patients with a known current or prior malignancy before committing to surgical intervention.